2016
DOI: 10.1002/ece3.2385
|View full text |Cite
|
Sign up to set email alerts
|

The influence of variability in species trait data on community‐level ecological prediction and inference

Abstract: Species trait data have been used to predict and infer ecological processes and the responses of biological communities to environmental changes. It has also been suggested that, in lieu of trait, data niche differences can be inferred from phylogenetic distance. It remains unclear how variation in trait data may influence the strength and character of ecological inference. Using species‐level trait data in community ecology assumes intraspecific variation is small in comparison with interspecific variation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Differences in functional rarity metrics across thermal preferences could indicate whether warming temperatures, expected to favor warm-water adapted species and lead to declines in cool and cold-water adapted species (Chu et al, 2005;Poesch, Chavarie, Chu, Pandit, & Tonn, 2016), will increase or decrease functional diversity. Furthermore, fish body size is related to many aspects of fish ecology including reproduction (Blueweiss et al, 1978) and dispersal (Radinger & Wolter, 2014), among others (Woodward et al, 2005;Alofs, 2016), and has also been used to predict vulnerability to predation (Alofs & Jackson, 2015) and shifts in species distributions under changing climate (Alofs, Jackson, & Lester, 2014). Finally,…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Differences in functional rarity metrics across thermal preferences could indicate whether warming temperatures, expected to favor warm-water adapted species and lead to declines in cool and cold-water adapted species (Chu et al, 2005;Poesch, Chavarie, Chu, Pandit, & Tonn, 2016), will increase or decrease functional diversity. Furthermore, fish body size is related to many aspects of fish ecology including reproduction (Blueweiss et al, 1978) and dispersal (Radinger & Wolter, 2014), among others (Woodward et al, 2005;Alofs, 2016), and has also been used to predict vulnerability to predation (Alofs & Jackson, 2015) and shifts in species distributions under changing climate (Alofs, Jackson, & Lester, 2014). Finally,…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Investigators often turn to available databases for data on species traits, such as FishBase (Froese and Pauly 2020), FishTraits (Frimpong and Angermeier 2020), and FishLife (Thorson et al 2017), to meet these data demands. Collectively, Cordlandwehr et al (2013) and Alofs (2016) suggest that the accuracy of specieslevel traits retrieved from such databases depends on the level of aggregation (or scale of data collection), the plasticity of the traits, the habitat the traits were retrieved from, and sampling bias. For example, Alofs (2016) found that the maximum size of small prey fishes recorded during field sampling was often larger than the maximum size recorded by other sources.…”
Section: Addressing Limitationsmentioning
confidence: 99%
“…Furthermore, the lack of important contextual information about measurement environmental context or levels of variation and replication for trait data limits such compilations. Yet, functional traits are environment-dependent 20 and display variability at the interpopulational level 21 . Therefore, a database hosting detailed information about functional traits and their environmental measurement context, which are required for aquaculture purpose, is still lacking.…”
Section: Background and Summarymentioning
confidence: 99%